Agricultural plastics as marine pollutants: Empirical evidence from inland and coastal field surveys - Carmen Morales-Caselles; Josué Viejo; Enrique Montero; Andrés Cózar (iScience)
Summary: Despite ongoing negotiations to establish a Global Plastics Treaty aimed at ending plastic pollution, agriculture remains an often-overlooked source of marine litter. While most global assessments emphasize take-out consumer activity and fishing as dominant contributors, these broad analyses may fail to capture regionally relevant sources. Here, we conducted field sampling across coastal and inland transects using a combination of shoreline surveys, dry riverbed inspections, and marine debris collection to quantify and classify plastic waste linked to agricultural activity. Our results show that agricultural plastic debris is prevalent even over 100 km downstream of cultivation hotspots. We identify dry riverbeds in agricultural landscapes as transient reservoirs that trap plastic during dry seasons, releasing large quantities into marine environments during episodic rainfall events. These findings underscore the need for management strategies that incorporate agriculture as a significant source of marine plastic pollution, particularly considering the projected rise in agricultural plastic use.